Prospects for the development of small molecular weight compounds to replace anti-tumour necrosis factor biological agents. - Foxwell, B; Andreakos, E; Brennan, F; Feldmann, M; Smith, C; Conron, M (2003)
The advent of anti-TNF biological agents has been a massive advance in our treatment of RA and other inflammatory diseases. However, it is acknowledged that there are major drawbacks, the greatest being cost. There is, therefore, clearly a massive market for small molecular weight inhibitors that would achieve similar effects to those of the biological agents. However, the effectiveness and safety of the biological agents has raised a very large hurdle that will need to be overcome if the potential cost benefit of such an inhibitor is to be realised.